Imidazole-2-carboxaldehyde Chitosan Thiosemicarbazones and their Copper(II) Complexes: Synthesis, Characterization and Antitumorigenic Activity against Madin-Darby Canine Kidney Cell Line - Sharan Adhikari, Hari; Garai, Aditya; Khanal, Chetana; Adhikari, Rameshwar; Nath Yadav, Paras (Asian Journal of Chemistry, 2021)
Chitosan oligosaccharide and high molecular weight crab shell chitosan were functionalized as imidazole-2-carboxaldehyde chitosan thiosemicarbazones and their copper(II) complexes were synthesized. The synthesized compounds were characterized by FT-IR, 13C NMR, EPR spectroscopy, powder X-ray diffraction (PXRD) analysis, elemental analysis and magnetic susceptibility measurements. The low molecular weight chitosan thiosemicarbazones showed higher in vitro inhibitory activity as studied by MTT assay against the tumorigenic epithelial Madin-Darby Canine Kidney (MDCK) cell line than the corresponding high molecular weight chitosan derivative. The antitumorigenic enhancement upon the complex formation was revealed by the better inhibitory activity of copper(II) chitosan thiosemicarbazone chelates.